Analysis of axial and overturning ultimate load-bearing capacities of deep groove ball bearings under combined loads and arbitrary rotation speed. (March 2022) - Xu, Hongyang; Wang, Pengfei; Ma, Hui; He, Duo; Zhao, Xiang; Yang, Yang
Highlights: An improved algorithm for solving the quasi-static model is proposed. The proposed method has very low sensitivity to the condition of initial values. A method for calculating the ultimate load-bearing capacities is proposed. The proposed method can be used to combined loads and arbitrary speed conditions. The effects of parameters on the ultimate load-bearing capacities are discussed. Abstract: In addition to radial force, deep groove ball bearings inevitably bear a certain degree of axial force and overturning torque under actual working conditions. Excessive axial force and overturning torque may make part of balls exceeding the rib of the raceway and accelerate the damage of the bearing. Therefore, a method for calculating the axial and overturning ultimate load-bearing capacities of deep groove ball bearings under combined loads and arbitrary rotation speed based on the quasi-static model is proposed. In the process of solving the quasi-static model, a Newton-Raphson method based on the analytical Jacobian matrix is adopted, which significantly reduces the difficulty of selecting the initial values, and the sensitivity of initial values is analyzed. Compared with the traditional method, the accuracy of the proposed calculation method of ultimate load-bearing capacities is verified. In addition, the effects of different factors such as radial force, bearing geometric parameters (radial clearance, raceway curvature, and rib height), and rotation speed on the ultimate load-bearing capacities are discussed. The results show that the radial force and bearing geometric parameters significantly change the ultimate load-bearing capacities. However, the effect of rotation speed is weak.